A study on the reading strategies of a selected group of tertiary students / Roslinda Abdul Wab - Abdul Wab, Roslinda (2006)
The important impact of reading strategies on second language reading has been acknowledged by many researchers for decades. The current study addresses two research questions: (1) What are the types and the frequency of strategy use dominating the students' approach to reading? (2) Is there a relationship between reported strategy use and reading achievement? 50 subjects of a selected group of ESL tertiary learners participated in this study. The Reading Strategy Questionnaire (Puvaneswary, 2001 and Monos, 2003) was adapted for use in this research. The adapted RSQ contained 25 items that measure the frequency and types of strategy use by the students. The items were subdivided into three macro-strategies: Global (G), Problem-Solving (PS) and Support Strategies (S). A TOEFL reading comprehension test was also employed to seek students' achievement in reading. The study conceived interesting results. It has proven that the selected students adopted all three types of strategies. Advanced students mainly employed support strategies, in comparison to their use of problem-solving and global strategies. They, however, displayed strategic use of these strategies (top-down and bottom-up strategies). Elementary and intermediate students, on the contrary, showed poor and infrequent use of all three reading strategies. They frequently utilized problemsolving and support strategies (bottom-up strategies) which explained their low reading achievement. The important impact of reading strategies on second language reading has been acknowledged by many researchers for decades. The current study has the following suggestions: (1) students' awareness on the important-use of reading strategies should be raised, (2) students should be taught on how to use these strategies, strategically, (3) students should be encouraged and trained to report on their strategy use while reading, (4) trainers or teachers must frequently motivate their students because highly-motivated students will become better or strategic readers.